Correction: Environmental Vulnerability Profiles and Suicidal Ideation Among Chinese Adolescents: The Mediating Role of Depression and Anxiety...Luo J, Gao R, Huang B, et al. Environmental Vulnerability Profiles and Suicidal Ideation Among Chinese Adolescents: The Mediating Role of Depression and Anxiety. Applied Research in Quality of Life. 2026;21(3):1681-1700 - Luo, Jiaxian; Gao, Ruixiang; Huang, Bingni; Guo, Yongxing; Luo, Pinchao (Applied Research in Quality of Life, 2026)
This correction notice addresses updates to a research article on quality of life, including the addition of a co-first author statement recognizing Jiaxian Luo and Ruixiang Gao as equal contributors. It also provides a revised funding statement detailing support from various Chinese provincial and national philosophy, social sciences, and science programs, clarifying that funders had no role in the study’s design or publication. Additionally, the ethics approval number (SCNU-PSY-2024-531) and approval date (24 February 2024) from the institutional research ethics committee have been included. The publisher affirms neutrality regarding jurisdictional claims.